Design and Engineering Test of Soil Filling Pile with Spiral Cone Foundation. Issue 1 (May 2020) - Fang, Ming; Fang, Guangxiu; Zhao, Shifan; Liu, Shoujin
Abstract: In this paper, through the comparative analysis of two different types of pile foundations, long auger bored cast-with-pressure concrete pile and Soil filling pile with spiral cone at the same engineering project and the same geological conditions in Western Liaoning Province, it is concluded that the soil filling pile with spiral cone compare with the long auger bored cast-with-pressure concrete pile, have obvious technical advantages in construction period and guarantee, reduce the construction expenditure. Moreover, the pile integrity testing is good, and has achieved good economic and social benefits. It is a new type of energy-saving and emission-reducing pile foundation with wide application prospects.